STRATEGI GURU ALQURAN HADIST DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MIN 1 KOTA MALANG - Umi Nafisatul Qoyyimah; Moh. Eko Nasrullah; Kukuh Santoso (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The use of teacher strategies, especially in the Quran Hadith course in MIN1 Malang, was effective and enjoyable for the students. The focus of the study is on planning, implementing and assessing teacher strategies to motivate students studying in the Quran Hadith courses in MIN 1 Malang City. To achieve this goal, researchers use a qualitative approach in interviews and types of research that generate data from documents when collecting data to provide a summary or presentation format for research reports. .. Researchers found research results from plans, such as the existence of a curriculum, learning of implementation plans, and learning of the media. Implementations include preparatory activities, core activities with a scientific approach, and final activities. Assessments include cognitive, emotional, and psychomotor aspects.